An experimental evaluation of cucumber (cucumis sativus) juice-fortified extenders: effects on semen motility, viability, and microbial dynamics in clarias gariepinus - Adebola Ajiboye; Timilehin Itadare; Olanrewaju Olaifa; Foluke Jemilehin; Opeyemi Ogundijo (Universitas Airlangga, 2026)
Conventional semen extenders are often inaccessible to smallholder aquaculture because of their high costs and infrastructure requirements, while bacterio-spermia and oxidative damage further compromise sperm quality during storage This study evaluated a cucumber juice-based semen extender supplemented with egg yolk and dextrose saline for preserving Clarias gariepinus semen at room temperature (25–28 °C). Semen from 15 males (three pools of five fish each) was diluted at a 1:2 ratio into three treatments: Control (30% cucumber juice), Extender A (30% cucumber juice, 25% dextrose saline, 5% egg yolk), and Extender B (30% cucumber juice, 15% dextrose saline, 15% egg yolk). Sperm motility, viability, pH, and bacterial contamination were assessed at 0, 3, 6, and 9 hours. Control sperm lost motility within 3 hours, whereas Extender B maintained 62% motility and 68% viability at 3 hours, and 32% motility and 28% viability at 6 hours, outperforming Extender A. Extender B also maintained a higher final pH (6.33 ± 0.08 vs. 5.63 ± 0.12), indicating better buffering against metabolic acidification. This simple and cost-effective preservation protocol addresses a critical need in resource-limited aquaculture by enabling artificial fertilization without refrigeration, thereby supporting small-scale fish farmers. Although E. coli, Bacillus, Klebsiella, and Serratia progressively contaminated all treatments, sperm survival remained significantly longer in Extender B. While fertility was not evaluated, sperm quality indicators suggest suitability for artificial fertilization. Overall, a cucumber juice-based extender containing 15% egg yolk effectively preserved functional C. gariepinus sperm for up to 6 hours at ambient temperature, providing a simple, low-cost protocol for artificial fertilization without refrigeration in resource-limited aquaculture.